Perilaku Konsumsi Santri Al-Jihad Surabaya ditinjau dari Perspektif Ekonomi Islam - Khoirul Mutholibin; Bagus Yuli Handoyo; Atti’udin Robbi (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
This article discusses the consumption behavior of students at Pondok al-Jihad Surabaya. Consumption is a human need that is vital for survival, without eating humans cannot move properly and socialize with others. The main purpose of consumption is to worship Allah SWT. Consumption must be based on the principles of the Qur'an and Hadith. This paper describes how many consumption characteristics the students have, who are also students of UIN Sunan Ampel. The data was conducted by interviewing 10 male and 10 female students. The data obtained were analyzed with the theory of consumer behavior in Islamic economics. The results of the study concluded that there were differences in consumption behavior between male and female students of Pondok al-Jihad Surabaya. The allowance for male students ranges from 500,000-1,000,000 rupiah, while the allowance for female students ranges from 900,000-1,700,000 rupiah. The money is used to meet basic needs, while the rest of the male students use it for coffee and cigarettes, while the female students use it for shopping, and if there is any leftover the money will be saved. Based on the Islamic economics, the consumption value of Pondok al-Jihad students is still reasonable, but for non-essential needs, the consumption should be reduced, such as the need for cigarettes, snacks, and shopping, so that they are not excessive because Islam prohibits excessive consumption.